2004
DOI: 10.5194/angeo-22-1665-2004
|View full text |Cite
|
Sign up to set email alerts
|

Observation of periodic fluctuations in electron and ion temperatures at the low-latitude upper ionosphere by SROSS-C2 satellite

Abstract: Abstract. The electron and ion temperature at the lowlatitude ionosphere exhibits a wide variety of fluctuations. Observations using SROSS-C2 satellite RPA payload during 1995-2000 provide an excellent opportunity to study the fluctuations in T e and T i in the upper ionosphere and to understand the dynamic processes existing at those altitudes. The spectral analysis of electron and ion temperatures using Fourier and wavelet techniques reveal the presence of quasiperiodicities, such as 14-day, 19-day, 27-day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The paper reported that morning overshoot is stronger at higher altitudes. But, the SROSS‐C2 conducted most of its ionospheric measurements near India, in the geographic longitude (GLON) range of 50°E–100°E (Prabhakaran Nayar et al, , section 2). Furthermore, in every season the statistics were based only on several tens of days in total (and only during two passes per day; see Alexander, , Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…The paper reported that morning overshoot is stronger at higher altitudes. But, the SROSS‐C2 conducted most of its ionospheric measurements near India, in the geographic longitude (GLON) range of 50°E–100°E (Prabhakaran Nayar et al, , section 2). Furthermore, in every season the statistics were based only on several tens of days in total (and only during two passes per day; see Alexander, , Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…Bhuyan et al (2004) further examined the diurnal, seasonal and latitudinal variation of ion temperature at 500 km and reported latitudinal gradients in T i during the period of morning and afternoon enhancement. Prabhakaran Nayar et al (2004) using SROSS C2 data for the period 1995-2000 examined the periodicities in electron and ion temperature and found periodicities ranging from 14 days (short) to 1.3 years (long) in both T e and T i . Zhang and Holt (2004) have studied the climatology of plasma temperature and the relationship between T e and N e from the long term data base of the Millstone Hill radar.…”
Section: Introductionmentioning
confidence: 99%
“…Schunk and Nagy (1978) had reviewed the local time, altitude and latitudinal variation of the electron and ion temperature in the F-region. Some interesting features of the low latitude ionosphere such as the morning and afternoon enhancement, the temperature and wind anomaly, latitudinal asymmetry, and short and long term periodicities have been observed and extensively studied (Brace and Theis, 1981;Oyama et al, 1996;Watanabe et al, 1995;Balan et al, 1997;Bhuyan et al, 2002aBhuyan et al, , b, 2004Prabhakaran Nayar et al, 2004). Brace and Theis (1981) used Atmospheric Explorer C satellite data to derive a model of electron temperature and found low nighttime temperature followed by a morning peak, a daytime plateau and a secondary evening enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the morphology and mechanisms of the ∼27 day variation of N m F 2 . There have been many studies of N m F 2 variations with this periodicity [e.g., Bartels , 1950; Titheridge , 1973; Kane et al , 1995; Forbes et al , 2000; Rishbeth and Mendillo , 2001; Pancheva et al , 2002; Rich et al , 2003; Prabhakaran Nayar et al , 2004; Wang et al , 2007; Oinats et al , 2008; Astafyeva et al , 2008; Afraimovich et al , 2008; Liang et al , 2008; Hocke , 2008; Min et al , 2009; Borries and Hoffmann , 2010]. However, the latitudinal, seasonal, local time, and solar cycle changes of this variation are not fully understood.…”
Section: Introductionmentioning
confidence: 99%